Optimal design of subsurface conveyance system based bio-ecological drainage system simulation - Lai, Sai Hin; Chin, Ren Jie; Soo, Eugene Zhen Xiang; Lloyd Ling; Hamed Benisi Ghadim (Springer Verlag, 2024)
As urbanization grows in size, the problems of flash floods and water pollution are expected to worsen, so viable and cost-effective solutions are essential to reduce the impacts. The Bio-Ecological Drainage System (BIOECODS) was developed to demonstrate the use of ‘control at source’ approaches to urban stormwater management. This research attempts to analyse the optimal design of a subsurface conveyance system (modular conduit) that is available in a case study with a BIOECOD project. This modelling exercise uses a novel technique to merge the surface and online subsurface flow. Through the InfoWorks SD software, the BIOECODS model has been calibrated and validated using rainfall events with different intensities, rainfall amounts, and durations. The developed model was then further analysed to obtain the optimum design of online subsurface modular conduit in the BIOECODS project, according to different scenarios. The results show that the subsurface modular conduit in the study area has an optimal size of 0.45 m height and is capable of attenuating peak flow at the downstream outlet by more than 60%. It is expected that the innovative modelling technique and the optimum design of an online subsurface conveyance system can be of interest to the community.